Recent advances on postharvest technologies of bell pepper: A review - Quazeem Omotoyosi Tiamiyu; Segun Emmanuel Adebayo; Nimat Ibrahim (Heliyon, 2023)
The bell pepper (Capsicum annuum L.) is a commercially important horticultural crop grown in tropical and sub-tropical areas across the world. Despite this importance, it is a perishable vegetable with a limited shelf life and high disease susceptibility. Bell pepper output has expanded significantly in recent years. However, this crop is still experiencing close to 40% postharvest losses annually. Chemical fumigation for postharvest disease control of bell pepper has been shown to be efficient against fungal infections, but environmental impact and consumption hazards limit its full use. Recently, non-chemical techniques including biological and botanical methods, non-destructive technologies and Artificial intelligence have been demonstrated to be effective as postharvest management of bell pepper. The paper provides exciting information on recent and emerging techniques for curtailing these losses in bell pepper, alongside their mechanism and existing benefits. The current limitations of these techniques as well as recommendations for potential applications are also addressed.